ANALISIS PENERAPAN METODE DEMONSTRASI OLEH BUDI HARIYANTO PADA PEMBELAJARAN SENI RUPA DI SMA NEGERI 1 PADEMAWU PAMEKASANANALISIS PENERAPAN METODE DEMONSTRASI OLEH BUDI HARIYANTO PADA PEMBELAJARAN SENI RUPA DI SMA NEGERI 1 PADEMAWU PAMEKASAN - Rahmatullah, Setiawan; Zaini, Imam (Jurnal Seni Rupa, 2022)
Abstract Budi Hariyanto is an art teacher who has been teaching using the demonstration method for more than 20 years, besides that he is also active in creating and exhibiting. This is what makes researcher interested in analyzing the demonstration method that Budi Hariyanto did. The purpose of this study is to describe the planning, implementation, and learning outcomes of the demonstration method that conducted by Budi Hariyanto in the fine arts subject at SMA Negeri 1 Pademawu. The study used a descriptive qualitative method approach, data collection technique use the methods of observation, interview, and documentation. The validity of the data using triangulation and informant review. Data analysis technique with reduction, presentation, and verification data. The study result showed that in planning the implementation of the demonstration method, Budi Hariyanto only prepare a Lesson Plan (RPP), learning media and teaching material. In the implementation process, Budi Hariyanto allocates one meeting a week with an allocation of 2 x 45 minutes, divided for theoretical and practical material. The result of learning have a considerable influence on the enthusiasm of students in learning fine arts, that is because the learning that carried out is very interesting and fun for students. Keywords: Budi Hariyanto, Demonstration method, Learning